2021
DOI: 10.3390/jpm12010008
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Response and Predictive Biomarkers for the Checkpoint Inhibitors in Castration-Resistant Metastatic Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Recently, checkpoint inhibitors have been investigated in metastatic prostate cancer, however their overall effect is unclear and needs to be further investigated. Objectives: The aim of this systematic review is to investigate the oncological response of metastatic castration-resistant prostate cancer patients to immune checkpoint inhibitors. Methods: Based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement, a systematic review of the literature was conducted through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Consistent with the results of recent studies the risk factor immune response was found to be related to aggressive prostate cancer progression and resistance to drug treatment ( 24 26 ), which may further direct urologists for grey zone aggressive prostate cancer early risk stratification. Functioning as one of the tumor necrosis factor ligand family, TRAIL has been reported to induce apoptosis in tumor cells preferentially.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the results of recent studies the risk factor immune response was found to be related to aggressive prostate cancer progression and resistance to drug treatment ( 24 26 ), which may further direct urologists for grey zone aggressive prostate cancer early risk stratification. Functioning as one of the tumor necrosis factor ligand family, TRAIL has been reported to induce apoptosis in tumor cells preferentially.…”
Section: Discussionsupporting
confidence: 87%
“…The m7Gscore was significantly positively related to TMB and several immune checkpoints expression (PDCD1, CD274, PDCD1LG2, TIGIT, IDO1, and CTLA4). Immunotherapy is more likely to respond effectively to PCa patients with a high level of TMB or immune checkpoints ( 48 , 49 ). Then we assessed the sensitivity to chemotherapy and endocrine drugs in the m7Gscore-defined groups.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even when compared to existing predictive markers such as TMB and PD-L1 expression, DDR mutation demonstrates an excellent prognostic effect [ 20 , 22 , 47 , 48 ]. In addition, DDR status predicts different clinical outcomes between immunotherapy and non-immunotherapy [ 20 , 72 ].…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
“…Among the patients treated with ICB, those with homologous recombination deficiency (HRD) or DDR mutation exhibited better response [13,47]. For patients with gastrointestinal cancer, advanced urothelial cancer, and metastatic prostate cancer treated with anti-PD-(L)1, DDR changes can lead to the prolongation of overall survival (OS) and progression-free survival (PFS) [47,48]. Furthermore, as the number of DDR changes increases, the objective response rate (ORR) and the durable clinical benefit (DCB) increased significantly [47,49].…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
See 1 more Smart Citation